Aerial and Respiratory Atmospheres of Avicenna’s Flying Person - Berndtson, Petri (Poligrafi, 2021)
Persian philosopher Avicenna (980‒1037) is famous for his thought experiment concerning the flying person,” “floating person” or “person suspended in air.” In this thought experiment, a person is created flying in the air in a state of total sensory deprivation. Scholars have debated for centuries what this thought experiment is all about. Most scholars have interpreted this thought experiment as essentially being about the existence of the soul (al-nafs) in its immateriality, substantiality, and self-awareness, as well as about the difference between the soul and the body. In my article, I will interpret Avicenna’s thought experiment in a totally different manner within the atmospheres of air and breathing. In my reading, I will carefully examine the fact neglected by scholars that this flight happens in the air and that it is the air that defines the existence of the flying person. With this aerial attitude I will argue that this thought experiment is not above all about the soul, but about air and al-nafs as a respiratory self. In my aerial and respiratory interpretation of Avicenna’s flying person, I will use Gaston Bachelard’s phenomenologically oriented aerial thinking as well as etymological analysis of al-nafs.